The history of the church in art - Giorgi, Rosa. (Los Angeles : J. Paul Getty Museum, 2008)
"The aim of this guide is to explain features and symbols in religious works of art as they relate to the history of the Church at the time these works were commissioned and created."--Introduction.
Introduction -- Liturgical objects and furnishings -- Clothes, vestments, and status -- Worship and images -- Episodes in the history of the western church -- Historical figures in the Roman church tradition -- Appendixes -- Index of subjects -- Index of artists.
Includes indexes.
Keywords: Christian art and symbolism -- Handbooks, manuals, etc; Christian art and symbolism